Students' responses to learning multimedia on the human digestive system during Covid-19 Pandemic - I Wayan Merta; Kusmiyati Kusmiyati; Johanes Purwadi (Jurnal Pijar Mipa, 2022)
This study aimed to determine students' satisfaction with learning multimedia on the human digestive system topic at a public high school (SMA Negeri 1 Praya Tengah). This study applied a quantitative approach with a survey method. The population in this study were students of class XI MIPA SMA Negeri 1 Praya Tengah. Meanwhile, the sample was determined by purposive sampling with the category of students using multimedia learning media on human digestive material. Therefore, the sample was 35 students from class XI MIPA 3. The data on students' satisfaction was conducted using a Likert-scale questionnaire instrument. The data analysis technique used was calculating the percentage of the data and then interpreting the data percentage score. The results of data analysis showed that the level of students' satisfaction was 94.14%, with the interpretation in the category of very satisfying. It can be concluded that students are very satisfied with multimedia learning media on the human digestive system material at SMA Negeri 1 Praya Tengah.